CLINICAL CASE OF TREATMENT OF INVASIVE UROTHELIAL CANCER OF THE UPPER URINARY TRACT. PROBLEMS OF COMBINED TREATMENT - A. A. Klimenko; I. P. Kostyuk; O. B. Karyakin; S. A. Moserov; Z. N. Shavladze; I. N. Zaborsky; V. S. Chaykov; M. E. Tarasova (Исследования и практика в медицине)
This article presents a clinical observation of the treatment of recurrent invasive urothelial cancer of the upper urinary tract using surgical and chemotherapy treatments. During the treatment, surgical treatment and 2 chemotherapy lines were performed. The patient was under strict dynamic control, during which diagnostic procedures were carried out, which allowed time to identify the progression of the underlying disease and prescribe timely treatment of identifi ed relapses.At the first stage, the patient underwent surgical radical treatment to remove the primary tumor focus localized in the lower third of the right ureter. At the control examination a local relapse was revealed. The 1st line of chemotherapy was prescribed and performed, against which the full effect of the treatment was noted. But in the future, the progression of the disease was revealed, which required the 2nd line of chemotherapy with preliminary surgical removal of a local relapse.